Evaluation of Eye Movements Pattern during Reading Process in Patients with Glaucoma: A Microperimeter Study. Issue 3 (May 2014) - Cerulli, Angelica; Cesareo, Massimo; Ciuffoletti, Elena; Montanaro, Maria Lucia; Mancino, Raffaele; Mirisola, Concetta; Sorge, Roberto; Cedrone, Claudio; Nucci, Carlo; Cerulli, Luciano
Purpose: To assess eye movements pattern during reading process in patients with primary open-angle glaucoma (POAG) using a microperimeter. Methods: Thirty-two patients with POAG at early and moderate stage, according to Glaucoma Staging System 2, and 34 healthy age- and sex-matched subjects were included in the study. Reading speed and accuracy were previously evaluated with specific tests adjusted for age. In addition, all participants performed a reading test with Microperimeter Nidek MP1. Ocular movements during the reading process were recorded and values of maximum and minimum eye movements along the horizontal (Xmax and Xmin) and vertical (Ymax and Ymin) axis and mean ocular movement speed were provided by the MP1. Results: There were significant differences between patients with and without POAG in terms of Xmax and Ymax eye movement values (4.75 ± 2.57 versus 3.38 ± 0.67, p = 0.003; and 4.39 ± 1.43 versus 3.34 ± 0.52, p<0.001, respectively). These differences were significant even comparing only stage 1 patients to controls. There were no significant differences in Xmin and Ymin values and mean ocular movement speed between the 2 groups. Conclusions: The study showed significant differences in eye movements pattern in patients with POAG during the reading test performed with the MP1 when compared to the control group. These alterations may be partly the consequence of the neurodegenerative process of the central visual pathway in glaucoma.